Contemporary socio-economic characteristics of transboundary cooperation between Ukraine and the Republic of Poland - Valentyna Obodovska; Yaroslav Oliynyk (Kazimierz Wielki University, 2017)
Very important role in the formation of a strong and effective foreign economic relations, regional policy and sustainable socio-economic development of Ukraine and The Republic of Poland plays a transboundary cooperation. Transboundary cooperation as a tool for increasing the competitiveness of border areas and accelerate the integration process factor plays a major role in improving socio-economic situation of both countries. The article is devoted to the characteristic of Ukrainian-Polish socio-economic cooperationon trans-borders ground. The state of foreign economic relations, dynamics of the the volume of GRP per capita and investment cooperation of Ukraine and The Republic of Poland is fixed.